Morphological and genetic characterization of marine filamentous cyanobacterium Geitlerinema isolated from Thailand - Tinpranee, Nichanan; Worananthakij, Worakrit; Incharoensakdi, Aran; Phunpruch, Saranya (My University, 2018)
Geitlerinema is a dominant benthic filamentous cyanobacterium found in the Gulf of Thailand and the Andaman Sea. We investigate the diversity of Geitlerinema strains isolated from Thailand using morphological and molecular characterization. No morphological differences were observed in the Geitlerinema isolates. Nucleotide sequencing and phylogenetic analyses of the 16S rDNA, the 16S–23S rRNA internal transcribed spacer (16S–23S ITS) and the cpcB-cpcA intergenic spacer (cpcB-cpcA IGS) showed that the marine Geitlerinema isolates belong to a single cluster that includes marine Geitlerinema sp. Flo1 and Geitlerinema sp. PCC7105 but is distinct from a type species, Geitlerinema splendidum and Geitlerinema strains which were recently transferred to the genus Anagnostidinema. From our results, it is confirmed that marine Geitlerinema differs from true freshwater Geitlerinema and is proposed to be a new genus in Oscillatoriales. In addition, using random amplification of polymorphic DNA (RAPD), the marine Geitlerinema isolates in this study could be classified into eight clades; however, this classification revealed no correlation with the geographic locations.
Keywords: 16S rDNA; 16S–23S ITS; CpcB-cpcA IGS; Genetic diversity; Marine Geitlerinema; Morphology; RAPD